Efficacy and Safety of Everolimus Plus Low‐Dose Tacrolimus Versus Mycophenolate Mofetil Plus Standard‐Dose Tacrolimus in De Novo Renal Transplant Recipients: 12‐Month Data. Issue 5 (4th January 2017) - Qazi, Y.; Shaffer, D.; Kaplan, B.; Kim, D. Y.; Luan, F. L.; Peddi, V. R.; Shihab, F.; Tomlanovich, S.; Yilmaz, S.; McCague, K.; Patel, D.; Mulgaonkar, S.
Abstract : In this 12‐month, multicenter, randomized, open‐label, noninferiority study, de novo renal transplant recipients (RTxRs) were randomized (1:1) to receive everolimus plus low‐dose tacrolimus (EVR+LTac) or mycophenolate mofetil plus standard‐dose Tac (MMF+STac) with induction therapy (basiliximab or rabbit anti‐thymocyte globulin). Noninferiority of composite efficacy failure rate (treated biopsy‐proven acute rejection [tBPAR]/graft loss/death/loss to follow‐up) in EVR+LTac versus MMF+STac was missed by 1.4%, considering the noninferiority margin of 10% (24.6% vs. 20.4%; 4.2% [−3.0, 11.4]). Incidence of tBPAR (19.1% vs. 11.2%; p < 0.05) was significantly higher, while graft loss (1.3% vs. 3.9%; p < 0.05) and composite of graft loss/death/lost to follow‐up (6.1% vs. 10.5%, p = 0.05) were significantly lower in EVR+LTac versus MMF+STac groups, respectively. Mean estimated glomerular filtration rate was similar between EVR+LTac and MMF+STac groups (63.1 [22.0] vs. 63.1 [19.5] mL/min/1.73 m 2 ) and safety was comparable. In conclusion, EVR+LTac missed noninferiority versus MMF+STac based on the 10% noninferiority margin. Further studies evaluating optimal immunosuppression for improved efficacy will guide appropriate dosing and target levels of EVR and LTac in RTxRs. Abstract : This 12‐month, multicenter, randomized, open‐label study in de novo renal transplant recipients reports statistically better graft survival, similar renal function, and comparable safety, despite missing the noninferiority margin of composite efficacy failure rate, with an everolimus plus low‐dose tacrolimus regimen versus mycophenolate mofetil plus standard dose tacrolimus.